Statement of Peer Review - Noor Hanita Abdul Majid; Agus Dwi Anggono; Waluyo Adi Siswanto; Tri Widodo Besar Riyadi; Nur Rahmawati Syamsiyah; Afif Faishal; Mohammad Sukri Mustapa (Engineering Proceedings, 2025)
In submitting conference proceedings to Engineering Proceedings, the Volume Editors of the proceedings would like to certify to the publisher that all papers published in this volume have been subjected to peer review by the designated expert referees and were administered by the Volume Editors strictly following the policies announced on the conference website [...]